ChemInform Abstract: Synthesis of Diverse Azolo[c]quinazolines by Palladium(II)‐Catalyzed Aerobic Oxidative Insertion of Isocyanides. Issue 37 (16th September 2014) - Vlaar, Tjoestil; Bensch, Lisa; Kraakman, Jasper; Vande Velde, Christophe M. L.; Maes, Bert U. W.; Orru, Romano V. A.; Ruijter, Eelco
Abstract The oxidative coupling of isocyanides with (2‐aminophenyl)oxazoles using air as the oxidant provides azolo[c]quinazolines (III) and (V) with high selectivity.